Evaluating the Effect of Embedded Responses in Multimedia-Based Instruction With Preservice Teachers. (November 2020) - Hirsch, Shanna E.; Chow, Jason C.; Randall, Kristina N.; Nemer, Shannon L.; McKown, Georgia
We report the findings of a randomized controlled trial examining the use of content acquisition podcasts for teachers (CAP-Ts) with 94 preservice teacher participants from two public universities. This study is an extension of a previous CAP-T study. We examined whether active embedded questions in CAP-Ts increased participant knowledge of functional behavioral assessments (FBAs). Participants completed a pretest, treatment, and posttest assessment to measure the extent to which CAP-Ts with active embedded questions supported participant knowledge, improved application of FBA skills, and impacted social validity as compared with traditional CAP-Ts. Findings indicate that CAP-T with embedded questions did not produce significant changes in preservice teacher knowledge and application of skills. Limitations and future directions are discussed.